Integrated PBL Approach Findings towards Physics Students’ Critical Thinking - Fauziah Sulaiman (2014)
This paper presents the findings of second phase of study on physics students’ critical thinking. This study was performed on a cohort of 25 (i.e., 13 females and 12 males) Physics with Electronics students from School of Science and Technology at University Malaysia Sabah. The sample was trained by an integrated Problem-Based Learning (PBL) method for 1 semester (i.e., 14 weeks). Participants’ critical thinking was evaluated using a previously validated instrument, the Watson Glaser Critical Thinking Appraisal (WGCTA) (i.e., inference; assumption; deduction; interpretation; evaluation arguments). The result shows that there is significant different in inference criteria (sig2-tailed, t=5.57, p=.00<*.05) favor to the first post test.